A Study on Technology Problems of Rural Industries in Madurai District (Global Journal of Management and Business Research, 2019)
The rural industrial sector stands next only to agriculture in terms of employment; on value addition its share is about fifty percent of the total value of goods produced in the manufacturing sector and in the matter of exports, its share is more than one third of the total exports made by the country. Outdated technology was a major problem for rural industries in the early years of Independence. Lack of technological improvement resulted in the production of articles which did not command wide consumer preference and they could fetch only low prices. Consequently, the earnings of rural industries were low. After the collection of data, the filled up interview schedules were edited properly. A master table was prepared to sum up all the data. With the help of the master table, classification tables were prepared and they were adopted directly for analysis. The suggestion based on the findings of the study for the growth and development of rural industries in Madurai district can be considered: Outdated technology was identified as a problem of rural industries. The study suggests that governments should redouble their efforts in the provision of infrastructure, especially in the area of technology upgradation of rural industries.
Keywords: rural industrial; technological; special skill; infrastructure and production